Meta-Analysis: The Influence of the PBL Learning Model on Students' Critical Thinking Ability in Physics Learning - Kamaluddin Kamal; Kamaluddin Kamal; AAIA Rai Sudiatmika; I Ketut Suma; I Nyoman Suardana; I Nyoman Suardana (Berkala Ilmiah Pendidikan Fisika, 2024)
The influence of the Problem Learning (PBL) model on students' critical thinking capacity in physics learning has been widely researched. The research aims to determine the effect size of each journal that will be used as a research sample. The method used in this research is meta-analysis, using ten journals as samples. OpenMEE was used to analyse data to obtain effect size values. The effect size test shows that the use of the PBL model has a general influence on students' critical thinking abilities of 2.191, which shows that the use of the PBL model has a very positive influence on students' critical thinking abilities in physics education. Using PBL in teaching and learning can improve students' analytical and problem-solving skills.